Creativity : seven keys to unlock your creative self - Gauntlett, David (Tantor Media, Inc., 2023)
This is a lively and thought-provoking book about how to do creativity, unlock your potential, and make a difference. The artists, musicians, and writers we think of as 'very creative' are just like us, except that they have spent time developing and realizing ideas and have found the confidence to share them with the world. None of this comes naturally. This wide-ranging book offers research, advice, and philosophy to fuel your understanding and passion for creativity. David Gauntlett draws on his own experiences of making music and experimenting with digital media alongside twenty-five years of researching creativity. Including insights from a diverse array of creators, this book highlights the vitality of the individual creative voice in a world where social media offers a weird mix of inspiration and suffocation, and our struggles for social justice are equally hopeful and upsetting. Creativity shows how vulnerability, experimentation, and courage can enable us to become bold and engaging creators.